Cultural Familiarity and Its Impact on Customer Satisfaction and Brand Awareness: A Study of Indonesian Restaurants in Taiwan - Mujahida, Sitti; Remmang, Hasanuddin; Azizurrohman, Muhammad (Journal of Marketing Innovation (JMI), 2024)
Indonesian restaurants in Taiwan face significant challenges in gaining recognition among the local population and international patrons, primarily due to cultural differences and limited marketing efforts. This study investigates the impact of food quality, service quality, pricing strategy, and marketing initiatives on patron satisfaction and brand recognition of Indonesian restaurants in Taiwan. It also examines how cultural familiarity moderates these relationships. A structured survey was conducted among 400 international patrons who dined at Indonesian eateries in Taiwan. Data were analyzed using Structural Equation Modelling (SEM) with Partial Least Squares (PLS) and moderation analysis. Findings reveal that food quality and pricing strategy significantly enhance customer satisfaction, while service quality and marketing efforts do not. Cultural familiarity strengthens the positive effect of food quality on satisfaction. This study underscores the importance of maintaining high food quality, implementing effective pricing strategies, and leveraging cultural familiarity for Indonesian restaurant owners in Taiwan. The research highlights the role of cultural factors in customer perceptions, contributing to the discourse on marketing strategies in the competitive food industry. The sample's focus on foreign customers in Taiwan may limit the broader applicability of the findings. Future research should consider factors like ambiance, location, and menu diversity for a comprehensive understanding of customer satisfaction and brand awareness.